Vegetation diversity of Hemaq Beniung Customary Forest, West Kutai, East Kalimantan - Swandari Paramita; Raharjo Ari Suwasono; Lasmito; Iya’ Setyasih; Ariyanto; Rachmad Mulyadi; Yohanes Budi Sulistioadi (Jurnal Penelitian Kehutanan Wallacea, 2022)
Indonesia is a biodiversity-rich country with the second-largest tropical forest in the world. One East KalimantanForest area in focus is the Hemaq Beniung Customary Forest. The Hemaq Beniung Customary Forest is the first customary forest with its license granted in East Kalimantan by the Ministry of Environment and Forestryof the Republic of Indonesia. Information on vegetation diversity is essential to ensure sustainable management of this forest area. This research provides such information through a survey with purposively chosen samples representing HemaqBeniung Customary Forest. The study reveals that the Importance Value Index of vegetation in different habitus (i.e., seedling, sapling, pole, and tree) are low, except for Elateriospermum taposBlume, which has a moderate value for the vegetation at the pole and tree habitus. The research also shows a high Richness Index (R), high Diversity Index’(H'), an almost evenly distributed Evenness Index (e), and a low Dominance Index (C). Syzygium borneensis(Miq.) Miq. and Knema elmeriiMerr. have the highest Importance Value Index for seedling and sapling habitus, respectively, while Elateriospermum taposBlume has the highest Species Significance Index for both pole and tree habitus. This study also found two dipterocarp tree species categorized as Critically Endangered (CR), namely Shorea johorensisFoxw. and Shorea lamellataFoxw. The presence of these CR species calls serious attention to managing the Hemaq Beniung Customary Forest mainly for hydrological function and conservation purposes while improving local communities' economy.